2016
DOI: 10.1016/j.riit.2016.11.002
|View full text |Cite
|
Sign up to set email alerts
|

The Out-of-Plane Bending Behavior of Brick Infill Walls Strengthened with Perforated Steel Plates

Abstract: The brick infill walls cease to contribute to the lateral strength and stiffness of a structure as soon as they fail in a brittle manner in the early stages of an earthquake. Recent studies indicated that the perforated steel plates externally bonded to both faces of a wall lead to two benefits. First, the increase in the lateral strengths and rigidities of the walls increase the overall lateral strength and stiffness of the structure. Secondly, the increase in the ductilities of the walls allows the walls to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Meanwhile, artificial intelligence techniques were introduced into the working behavior prediction of laterally loaded masonry walls by Mathew [17], Zhou [18], Zhang [19] and Gopinath [20]. Besides, new materials such as fiber-reinforced polymer (FRP) material were applied to improve the mechanical properties of masonry and the working performance of masonry column, beams and walls/slabs [21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, artificial intelligence techniques were introduced into the working behavior prediction of laterally loaded masonry walls by Mathew [17], Zhou [18], Zhang [19] and Gopinath [20]. Besides, new materials such as fiber-reinforced polymer (FRP) material were applied to improve the mechanical properties of masonry and the working performance of masonry column, beams and walls/slabs [21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Aykac [ 32 ] showed that perforated steel sheets are more capable than FRP to improve of infill wall. Experimental studies showed that the use of perforated steel plates improves OOP behavior of infill wall, but it does not prevent overall fracture of infill wall.…”
Section: Introductionmentioning
confidence: 99%